2013
DOI: 10.1007/s00106-013-2779-z
|View full text |Cite
|
Sign up to set email alerts
|

Zur Wahrnehmung verhallter Sprache mit Cochleaimplantaten

Abstract: The results of the current investigation indicated that reverberation results in decreased speech understanding of CI users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was also shown that late reflections mainly contributed to the decrease and that early reflections may not be detrimental to speech perception of CI users. Mühler and colleagues reported a significant decrease in speech perception scores in noise with increasing reverberation time in unilaterally tested CI users (co-located masker condition (29)). However, the results obtained are not comparable to the results of the presented study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that late reflections mainly contributed to the decrease and that early reflections may not be detrimental to speech perception of CI users. Mühler and colleagues reported a significant decrease in speech perception scores in noise with increasing reverberation time in unilaterally tested CI users (co-located masker condition (29)). However, the results obtained are not comparable to the results of the presented study.…”
Section: Discussionmentioning
confidence: 99%
“…Sound localization was assessed in a virtual auditorium with a size of 22 m  16 m  10 m. The mean reverberation time was 0.51 seconds, based on the small reverberation time used by Kerber and Seeber in 2013, who found effects of reverberation on localization in bilateral CI users (28). Speech perception was assessed in a virtual auditorium with smaller dimensions (size: 16.0 m  12.0 m  7.4 m) and the mean reverberation time was 1.2 seconds, as Mu ¨hler and colleagues found in 2014 that higher reverberation times resulted in higher effects of reverberation on speech perception (29).…”
Section: Room Simulationmentioning
confidence: 99%
“…Listeners with BCIs also demonstrated poorer speech understanding ability than listeners with NH in noise [4]. Regarding the reverberation effect, it was found that speech perception performance decreased as reverberation time increased and the performance started to be affected at 0.3-0.7 s reverberation time for listeners with unilateral cochlear implant (UCI) [7]. The adverse combined effect of noise and reverberation was found for listeners with UCI [8].…”
Section: Short Communicationmentioning
confidence: 99%